1997
DOI: 10.1002/(sici)1097-0193(1997)5:2<124::aid-hbm6>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Striatal recruitment during an implicit sequence learning task as measured by functional magnetic resonance imaging

Abstract: Prior research has repeatedly implicated the striatum in implicit sequence learning; however, imaging findings have been inconclusive with respect to the sub-territories and laterality involved. Using functional magnetic resonance imaging (fMRI), we studied brain activation profiles associated with performance of the serial reaction time task (SRT) in 10 normal right-handed males. Behavioral results indicate that significant implicit learning occurred, uncontaminated by significant explicit knowledge. Concaten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
169
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 283 publications
(191 citation statements)
references
References 25 publications
(38 reference statements)
22
169
0
Order By: Relevance
“…In humans, pathological degenerative processes affecting the striatum [as in Parkinson's (PD) or Huntington's (HD) diseases], or circumscribed damage to the cerebellum, have been shown to produce an impairment on various skill-learning tasks, especially in the visuomotor modality (e.g., Doyon, Gaudreau, Laforce, Castonguay, Bédard, Bédard, & Bouchard, 1997a;Ferraro, Balota, & Connor, 1993;Harrington, York Haaland, Yeo, & Marder, 1990;Heindel, Salmon, Shults, Walicke, & Butters, 1989;Saint-Cyr, Taylor, & Lang, 1988;Sanes, Dimitrov, & Hallett, 1990). These findings have been corroborated by studies with healthy control subjects using modern brain-imaging techniques such as positron emission tomography (PET) and functional magnetic resonance imaging (fMRI) in which hemodynamic changes have been observed in the striatum and/or the cerebellum during the incremental acquisition of visuomotor skills (e.g., Doyon, Owen, Petrides, Sziklas, & Evans, 1996b;Flament, Ellermann, Kim, Ugurbil, & Ebner, 1996;Grafton, Woods, & Mike, 1994;Jenkins, Brooks, Nixon, Frackowiak, & Passingham, 1994;Rauch et al, 1997).…”
Section: Introductionmentioning
confidence: 82%
“…In humans, pathological degenerative processes affecting the striatum [as in Parkinson's (PD) or Huntington's (HD) diseases], or circumscribed damage to the cerebellum, have been shown to produce an impairment on various skill-learning tasks, especially in the visuomotor modality (e.g., Doyon, Gaudreau, Laforce, Castonguay, Bédard, Bédard, & Bouchard, 1997a;Ferraro, Balota, & Connor, 1993;Harrington, York Haaland, Yeo, & Marder, 1990;Heindel, Salmon, Shults, Walicke, & Butters, 1989;Saint-Cyr, Taylor, & Lang, 1988;Sanes, Dimitrov, & Hallett, 1990). These findings have been corroborated by studies with healthy control subjects using modern brain-imaging techniques such as positron emission tomography (PET) and functional magnetic resonance imaging (fMRI) in which hemodynamic changes have been observed in the striatum and/or the cerebellum during the incremental acquisition of visuomotor skills (e.g., Doyon, Owen, Petrides, Sziklas, & Evans, 1996b;Flament, Ellermann, Kim, Ugurbil, & Ebner, 1996;Grafton, Woods, & Mike, 1994;Jenkins, Brooks, Nixon, Frackowiak, & Passingham, 1994;Rauch et al, 1997).…”
Section: Introductionmentioning
confidence: 82%
“…Some previous reports are in line with our results. Prefrontal activity has been reported in an implicit motor learning study, although the activity was only significant when a liberal threshold was used, and at that threshold, there was also activation in the visual cortex (Rauch et al, 1997). Moutoussis and Zeki (2002) have described a binocular masking paradigm (called binocular fusion) in which prefrontal activity was found to be higher when the volunteers did not see the presented figures.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, however, implicit and explicit processes were exclusively associated with different training phases-a procedure that does not ensure that implicit and explicit components were effectively dissociated during the two training conditions. In a PET scan experiment, (Peigneux et al, 2000) reported the systematic activation of the striatum when participants were presented with a complex probabilistic sequence (see also Rauch et al, 1997). Sequence learning in experiments using this material is typically essentially implicit (e.g., Jiménez, Méndez & Cleeremans, 1996).…”
Section: Discussionmentioning
confidence: 99%